The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1002/jbio.200900066
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting diffuse reflectance for in vivo skin reactions in terms of chromophores

Abstract: The measurement and quantification of skin reactions to insults involves certain assumptions about the relation between intensity of color appearance of the skin and the concentration of endogenous chromophores. The underlying assumption is that the Beer-Lambert law is obeyed, i.e., that a linear relation exists between the absorbance and the concentration of each chromophore and that the total absorbance is the linear superposition of the contributions of each chromophore. In this paper the authors compiled t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…(14), with triplets outside of the diffusion theory region omitted. (14), with triplets outside of the diffusion theory region omitted.…”
Section: Empirical Determination Of the Scattering Losses Correction mentioning
confidence: 99%
“…(14), with triplets outside of the diffusion theory region omitted. (14), with triplets outside of the diffusion theory region omitted.…”
Section: Empirical Determination Of the Scattering Losses Correction mentioning
confidence: 99%
“…1,2 Those chromophores can be altered in concentration either by external insults such as chemical irritants, UV radiation or by changes of physiological environment. Colorimetry has been used as an objective measure of perceived skin color by human eye to document and score physiological responses of the skin from the various external insults.…”
Section: Introductionmentioning
confidence: 99%
“…The optics of skin chromophores have been described in detail by Anderson and Parish. 7 The use of spectrophotometry of skin by many authors has shown good results in assessing melanin and hemoglobin, Masuda et al, 8 Stamatas et al, 9,10 Kollias et al, [11][12][13] Andersen et al, 14,15 Hegyi et al, 16 Verkruysse et al, 17 Hamzavi et al, 18 Taylor et al, 19 Bjerring et al 20 and Nielsen et al 21 The stimulus for this paper was to find a method to assess the efficacies of various vitiligo treatment modalities, by early signs of re-pigmentation.…”
Section: Introductionmentioning
confidence: 99%